PERINATAL OUTCOME IN WOMEN PRESENTING WITH REDUCED FOETAL MOVEMENT AT TERM - Ghani, Seema; Hasan, Shabnam; Ali, Fauzia; Nadeem, Shabnum (Journal of Ayub Medical College Abbottabad, 2024)
Background: foetal movements are one straightforward indicator of foetal health. The evidence, however, is still insufficient to warrant the inclusion of reduced foetal movements in national recommendations as part of a more comprehensive evaluation. The study objective was to determine perinatal outcome in women presenting with reduced foetal movement at term gestation. Methods: A prospective, observational study was conducted in Hamdard University Hospital Karachi during January 2021 to June 2021, 216 pregnant women with reduced foetal movement at term were recruited from outpatient clinics, wards and labour room triage. Data was collected regarding demographic and clinical features of mothers. Neonatal outcomes were also investigated. Results: Findings of the study revealed that 60.6% women had one episode and 39.4% women had two episodes of reduced foetal movements. 1/4th of the neonates were low birth weight, 1/5th of the babies had Apgar score less than 7 in five minutes, 9.3% neonates had cord around the neck and 1/3rd of the neonates were admitted to the NICU. Chi square test of association revealed that maternal factors such as maternal age, BMI, gravidity were significantly associated with reduced foetal movements. foetal outcomes such as NICU admission and presence of meconium were significantly associated. Conclusion: The present study analyzed that Episodes of RFM were significantly associated with age, BMI, gravidity of mother. RFM episodes was associated with increased risk of cord around neck among neonates of mother with repeated RFM episodes whereas NICU likelihood was higher among neonates of mother with single RFM episode.